Evaluation of colorectal cancer liver metastases based on liquid biopsy combined with folate receptor– Positive circulating tumor cells and HSP90 - Huang, Maosen; Cheng, Linyao; Mo, SiSi; Ru, Haiming; Mo, Xianwei; Yan, Linhai (Frontiers in Oncology, 2022)
Objectives: Colorectal cancer liver metastases (LMCRC) is a major cause of cancer-related death worldwide. We can only reduce the mortality rate by discerning the risk of liver metastases in patients with colorectal cancer at an early stage. Hence, we innovatively combined the use of folate receptor-labeled circulating tumor cells (FR+CTCs) and metastasis-related marker HSP90 to screen colorectal cancer patients and explore the prognostic factors of patients with high expression of FR+CTC and HSP90. Materials and Methods: A retrospective study of 356 patients with measurable colorectal cancer was included. Detection of FR+CTC and HSP90 in the blood of patients by liquid biopsy. Follow-up studies were conducted in time for the inclusion criteria of colorectal cancer patients. Results: FR+CTC and HSP90 were highly expressed in colorectal patients with liver metastases. The diagnostic ability of the combined ROC curve of FR+CTC and HSP90 (AUC=0.79, sensitivity=70.55%, specificity=92.66%) was significantly greater than that of a single index. The results of timely follow-up of patients showed that the high expression of FR+CTC significantly shortened the median disease-free survival (mDFS) of 36.5 months (95% CI: 14.13-58.87, Logrank p<0.0001) compared with the low expression cohort, and the mDFS of the HSP90 high expression cohort was significantly higher than that of the low expression cohort (Logrank p=0.0002), mDFS=58.47 months (95% CI: 37.12-79.81, Logrank p<0.0001). We performed univariate and multivariate analysis to show that FR+CTC and HSP90 were risk factors for MCRC disease progression, and then constructed a high and low risk score model of risk factors to evaluate MCRC. The diagnostic sensitivity of the risk model for MCRC was significantly improved (AUC=0.89, sensitivity=85.29%, specificity=81.33%), and the mDFS of patients in the high-risk group advanced to 33.28 months (95% CI: 27.24-39.31, Logrank p<0.0001). Conclusion: Colorectal cancer patients with high expression of FR+CTC and HSP90 are at risk of liver metastasis and suggest a poor prognosis. Combining the two indicators can improve the early screening and diagnosis of LMCRC patients. In addition, combining multivariate risk model can further assist patients in appropriate stratification and design tailored treatment regimens, but further validation is needed before routine clinical application.